Validitas Jual Beli Item Virtual dalam Game Online: Analisis Status Kepemilikan (Milkiyah) dan Risiko Gharar - ersa putri amanda; Andesta Yoga Purnama; M. Rifki Finando; Holijah Holijah (GLOBAL SCIENTS PUBLISHER, 2026)
The rapid growth of virtual item trading in online games has raised legal issues, particularly regarding the clarity of ownership status (milkiyah) and the potential for uncertainty (gharar) in transactions. This study aims to analyze the validity of such transactions from the perspective of Islamic law. This research employs a qualitative method with a normative approach. Data collection was conducted through literature review by examining Islamic legal sources including the Al-Qur’an, Hadith, fiqh principles, and the opinions of scholars. Data were also gathered from scientific literature, journals, and regulations governing digital transactions and the practice of trading virtual items in online games. Accordingly, the buying and selling of virtual items in online games can be deemed valid under Islamic law if it meets the principles of clear ownership and is free from elements of gharar. Conversely, if the transaction involves ambiguity and high risk, it is considered invalid.